Pest and disease incidence of coniferous species in Taman Saujana Hijau, Putrajaya urban park, Malaysia - Nura Adila Shamsul Kamar; Siti Khadijah Abd Rahim; Annya Ambrose; Norida Hanim Nha; Zaiton Samdin; Affendy Hassan; M. Nazre; Razak Terhem (Northeast Forestry University, 2023)
Taman Saujana Hijau (TSH), Putrajaya is a 41-ha urban park planted with various coniferous species from around the world. Insect pests and disease incidences of this park are unknown and there is a need for an evaluation of the health status of this urban park. This study assessed the level of pest and disease incidents of coniferous species in 12 plots of 7 species (Araucaria bidwilii, Araucaria haterophylla, Araucaria cunninghamii, Pinus caribaea, Pinus merkusii, Podocarpus polystachyus, and Podocarpus costalis). Termites, canker disease, and foliar disease are three major problems. The highest pest and disease incidence (PnDI) was foliar disease with a 0.49 coefficient correlation between the total number of trees and the PnDI, followed by canker disease with 0.40, and termites with 0.36. Of the seven conifers, A. haterophylla was the most infected followed by A. bidwilii and A.cunninghamii. It was concluded that the incidence of pests and diseases in TSH was moderate. To our knowledge, this may be the first baseline inventory of pests and diseases of coniferous species in Malaysia.